Cryopreserving turkey semen in straws and nitrogen vapour using DMSO or DMA: effects of cryoprotectant concentration, freezing rate and thawing rate on post-thaw semen quality. Issue 2 (3rd March 2016) - Iaffaldano, N.; Di Iorio, M.; Miranda, M.; Zaniboni, L.; Manchisi, A.; Cerolini, S.
Abstract: 1. This study was designed to identify a suitable protocol for freezing turkey semen in straws exposed to nitrogen vapour by examining the effects of dimethylacetamide (DMA) or dimethylsulfoxide (DMSO) as cryoprotectant (CPA), CPA concentration, freezing rate and thawing rate on in vitro post-thaw semen quality. 2. Pooled semen samples were diluted 1:1 (v:v) with a freezing extender composed of Tselutin diluent containing DMA or DMSO to give final concentrations of 8% or 18% DMA and 4% or 10% DMSO. The semen was packaged in 0.25 ml plastic straws and frozen at different heights above the liquid nitrogen (LN2 ) surface (1, 5 and 10 cm) for 10 min. Semen samples were thawed at 4°C for 5 min or at 50°C for 10 s. After thawing, sperm motility, viability and osmotic tolerance were determined. 3. Cryosurvival of turkey sperm was affected by DMSO concentration. Freezing rate affected the motility of sperm cryopreserved using both CPAs, while thawing rates showed an effect on the motility of sperm cryopreserved using DMA and on the viability of sperm cryopreserved using DMSO. Significant interactions between freezing rate × thawing rate on sperm viability in the DMA protocol were found. 4. The most effective freezing protocol was the use of 18% DMA or 10% DMSO with freezing 10 cm above the LN2 surface and a thawing temperature of 50°C. An efficient protocol for turkey semen would improve prospects for sperm cryobanks and the commercial use of frozen turkey semen.